Biotechnology to improve cassava - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
The production of cyanide by the cassava plant, possibly as a defence mechanism against pests, was one of the subjects under discussion at the first international scientific meeting of the Cassava Biotechnology Network (CBN) held in Colombia in...